Efektifitas Relaksasi Otot Progresif Terhadap Penurunan Tingkat Kecemasan Pada Pasien Luka Kaki Diabetik Di Kabupaten Bone - Alfian Mas'ud; Mardiana Mardiana (Jurnal Keperawatan Muhammadiyah, 2021)
Background: Diabetic foot ulcers are infection, ulceration and/or destruction of deep tissue, neurological disorders and various peripheral vascular diseases in the lower limbs. Sudden life changes make people with diabetic foot wounds show some negative psychological reactions.Purpose: This study was to determine the effectiveness of progressive muscle relaxation on reducing anxiety levels in diabetic foot ulcer patients.Methods: The research design used in this study was a quasi-experimental research design, namely pre-test and post-test control group. Researchers divided the sample into 2 groups, namely the control group was given deep breathing relaxation while the experimental group was given progressive muscle relaxation. Hypothesis testing was then carried out by testing the mean difference (ratio scale) of the anxiety level scores as measured by the HARS (Hamilton Anxiety Rating Scale) scale.Results: This study shows that the results of the Independent t-test showed that before the intervention was given there was no significant difference in anxiety in the two sample groups with p value = 0.181 > 0.05, but after the intervention was given the mean difference was 6.82 and p value = 0.001 < 0.05. which means that there is a difference in anxiety between the group given progressive muscle relaxation therapy and the group given deep breathing exercises.